Anxiety in Andalusian Poetry Examples from the Existential Reflections of Andalusian Poets - Shaalan Jalil Khudhair, Dr. (lark, 2026)
Abstract This research aims to explore the phenomenon of anxiety in Andalusian poetry by analyzing selected models from Andalusian poets, highlighting how this anxiety manifested in their existential reflections and psychological mirror. Initially, the concept of anxiety was examined as a profound human suffering, intertwined with feelings of fear, hesitation, and the search for meaning in life, expressing a state of internal tension and philosophical contemplation. Poetic samples from prominent Andalusian poets such as Ibn Zaydun, Ibn Khafajah, and Ibn Hamdis were reviewed, revealing that these poets wrote not only about love and beauty but also expressed fears of mortality, anxiety over the loss of hope, and discontent with the fluctuations of time and fate. This was reflected in their depiction of nature, events, and emotions in a way that mirrors their existential reflections and their expressions of tension between the desire for stability and fear of demise. The study demonstrated that anxiety in Andalusian poetry was not merely a transient state but a means of expressing a deep awareness of the inevitability of death, the impermanence of life, and the struggle between hope and despair, which imbued their poetry with a philosophical and existential dimension. Ultimately, Andalusian poetry serves as a reflective mirror of the existential tensions experienced by humans, expressed through a refined artistic style that combines poetic beauty with philosophical depth, remaining a vivid testimony to a rich human experience filled with emotions and existential reflections. Keywords: anxiety, Andalusian poetry, poets’ reflections, existence